Genetic diversity assessment of Poincianella pyramidalis (Tul.) L.P. Queiroz accessions using RAPD markers - Santos, J. S.; Mendes, S. S.; Conde, D. C.; Delmondez, R. C.; Mann, R. S.; Thomazzi, S. M. (Scientia Plena, 2012)
Over the long term, the ability of a species to respond adaptively to environmental changes depends on its genetic variability. Catingueira (Poincianella pyramidalis) is a tree species that has been used by the population for treat some diseases in the folk medicine. Genetic relationships among 13 Poincianella pyramidalis genotypes collected from different places of Sergipe – Brazil were investigated by using Randomly Amplified Polymorphic DNA (RAPD), in order to provide some information about its genetic diversity for restore programs. A total of 10 RAPD primers were used to investigate the genetic diversity and genetic relationships among different germplasms of 13 accesses of catingueira. It was found a similarity (average) of 0.70 between the studied genotypes. The highest and lowest detected similarities were 0.89 and 0.55, respectively. The calculated Jaccard index was 99%, so all genotypes are considered genetically different between themselves and this is good specially because if we consider that restore programs that needs species with some genetic variability, the P. pyramidalis showed that although its was found in a site with antropical changes it can resist to the genetic erosion and keeps its variability.